Penambahan Karaginan Terhadap Mutu Sirup Kulit Kayu Manis - Faruqi, Safraul; Ali, Akhyar; ', Rahmayuni (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
This study aims to determine the best concentration of carrageenan on the quality of cinnamon bark syrup. Research conducted experiments using a completely randomized design (CRD) with 7 treatment that K0 = without carrageenan ; K1 = Carragenan 1 %; K2 = Carragenan 1.2 %; K3 = Carragenan 1.4 %; Carragenan K4 = 1.6 %; Carragenan K5 = 1.8 %; K6 = Carragenan 2 %. The results showed that the concentration of carrageenan significantly affect the pH value, the viscosity of the sucrose concentration, homogeneity of the emulsion, the color of the hedonic test, the color and flavor of the descriptive test. Concentration K1 (addition of carrageenan 1 %) with a pH of 4.22; levels of sucrose 64.88 %; levels sinamaldehid 0.6429 %; viscosity 40.75 g/cm.s in the first week and 32.87 g/cm.s on the second week , the homogeneity of the emulsion 95.83 % in the first week and 94.17 % in the second week. Keywords : Syrup cinnamon bark, carragenan.